2018
DOI: 10.1007/s00520-018-4295-x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the safety and efficacy of aerobic exercise during cytotoxic chemotherapy treatment

Abstract: Exercise during chemotherapy is safe and should be encouraged because of beneficial effects on QoL and physical functioning. More research is required to determine the impact on chemotherapy completion rates and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…However, prehabilitation programs are also targeting non-surgical cancer patients receiving pharmacological treatment only, e.g., as chemotherapy and/or radiotherapy [15][16][17]. In this context, a recent meta-analysis on 3257 patients with cancer indicated that moderate aerobic exercise performed at 70-80% of maximum heart rate not only was feasible and safe but also showed beneficial effects in QoL and physical functioning and maintained or at least improved fitness during concomitant chemotherapy [18]. Although not without bearing a considerably risk of bias, pooled data from another recent metaanalysis revealed that prehabilitation significantly improved mood, physical well-being, and immune function for prostate cancer patients and improved fatigue and psychological outcomes with a trend indicating better QoL among breast cancer patients [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, prehabilitation programs are also targeting non-surgical cancer patients receiving pharmacological treatment only, e.g., as chemotherapy and/or radiotherapy [15][16][17]. In this context, a recent meta-analysis on 3257 patients with cancer indicated that moderate aerobic exercise performed at 70-80% of maximum heart rate not only was feasible and safe but also showed beneficial effects in QoL and physical functioning and maintained or at least improved fitness during concomitant chemotherapy [18]. Although not without bearing a considerably risk of bias, pooled data from another recent metaanalysis revealed that prehabilitation significantly improved mood, physical well-being, and immune function for prostate cancer patients and improved fatigue and psychological outcomes with a trend indicating better QoL among breast cancer patients [19].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity (PA) benefits people living with or beyond cancer by improving physical function and QoL during and after cancer treatment, and cancer-related outcomes like treatment completion, maintenance of, or faster return to, pretreatment health, fewer unnecessary healthcare visits and better survival rates [6,[17][18][19][20][21][22]. Improvements are greater in those engaging in PA sooner after a diagnosis [23].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of physical training in cancer patients may vary depending on tumor type, stage and exercise modalities. A systematic review analyzing the effectiveness of aerobic exercise during chemotherapy treatment in cancer patients, has shown beneficial effects in terms of both quality of life and muscle function [37] . In chemotherapy-treated breast cancer patients, exercise increases muscle fiber cross-sectional area, citrate synthase activity, mitochondrial complex protein levels and muscle capillarization [38] .…”
Section: Exercise As a Modulator Of Muscle Metabolismmentioning
confidence: 99%